Diseño de una red de datos basada en tecnología xg-pon systems (10 gigabit capable passive optical networks) para el programa de vivienda ciudad verde. - Sarango Sánchez, David Israel (2015)
The present project of titling proposes a telecommunications network based on PON technology for the Green City housing program of the Loja city. For the proposed design of the PON network, it based on the recommendation of the ITU-T G.987 taking features such as: the transmission rate up and down that the standard provides to, authentication from the ONT to the OLT, coexistences of XG-PON with G-PON, etc. It also took into account the regulations of outside plant design (ODN) by the National Telecommunications Corporation (CNT EP), maximum attenuation levels were allowed by the passive components for the most critical user. For the distribution of the fiber cable, the channeling underground type was chosen, since it is imposed on a compulsory basis for all GADs to contractors, operators and future programs of implantation of houses or buildings for the implementing of these telecommunications networks. The present assignment is divided into sections, which belongs to the part of literature review to achieve conclude the proposed design of the Network XG-PON data. Initially a description of the transmission medium of optic fiber is presented with its characteristics that display this means and techniques that are used for the transmission of large bandwidths. Then, the PON technology was described, allowing us to know what kind of access solution can be implemented in massive places with the transmission technology of the standard that proposes to. Then, the network design for the Green City Housing Program is carried out, taking into account the following structure: Knowing the current state of the housing program Designing the network OND Calculation of the optical balance for the network And calculation of bandwidth of the proposed services for the transmission to each end user. Next a legal framework is presented, which allows to know through the constitution of the republic and some regulations the GPON network design in Ecuador, mainly in Loja city. Then the requirements that must fulfill the both passive and active equipment for network design is specified, for later selecting the equipment offered by manufacturers, contrasting with the characteristics of the obtained design. After selecting the components and network equipment, a referential budget of the proposed design was developed. Finally, the analysis and discussion of the results obtained for the proposed network design was performed, as well as the statement of conclusions and recommendations about the research that were carried out for this titling project.